Vulpia (Gramineae) in Malesia - Alex - Sumadijaya; Jan Frits Veldkamp (Reinwardtia, 2009)
SUMADIJAYA, A. & VELDKAMP, J. F. 2009. Vulpia (Gramineae) in Malesia. Reinwardtia 12(5): 343–346. ⎯ A brief account of Vulpia (Gramineae) in Malesia is which consisting of V. bromoides and V. myuros is provided here, based on material seen primarily by JFV in BO, K, L, CANB.